Comparative efficacy and safety of JAK inhibitors in the treatment of moderate-to-severe alopecia areata: a systematic review and network meta-analysis - Yan, Ting; Wang, Ting; Tang, Mei; Liu, Nan (Frontiers in Pharmacology, 2024)
We performed a Bayesian network meta-analysis to indirectly compare the relative efficacy and safety of the latest JAK inhibitors for moderate-to-severe alopecia areata (AA). 13 trials totaling 3,613 patients were included. Two low-dose groups of oral formulations (ritlecitinib 10mg and ivarmacitinib 2mg) and two topical formulations (delgocitinib ointment and ruxolitinib cream) appeared to be relatively ineffective against moderate-to-severe AA. Ranking analysis suggested that brepocitinib 30mg has the best relative effect in reducing the SALT score (sucra=0.9831), and demonstrated comparable efficacy to deuruxolitinib 12mg (sucra=0.9245), followed by deuruxolitinib 8mg (sucra=0.7736). Regarding the SALT50 response, brepocitinib 30mg ranked highest (sucra=0.9567), followed by ritlecitinib 50mg (sucra=0.8689) and deuruxolitinib 12mg (sucra=0.7690). For achieving the SALT75 response, deuruxolitinib 12mg had the highest probability (sucra=0.9761), followed by deuruxolitinib 8mg (sucra=0.8678) and brepocitinib 30mg (sucra=0.8448). Deuruxolitinib 12mg might be the most effective therapy for patients with severe AA (sucra=0.9395), followed by ritlecitinib 50mg (sucra=0.8753) and deuruxolitinib 8mg (sucra=0.8070). Deuruxolitinib 12mg/8mg demonstrated notable efficacy for moderate-to-severe AA, and is expected to be a new treatment option for AA. It was worth noting that deuruxolitinib exhibit a greater likelihood of causing adverse events in comparison to other JAK inhibitors.Ritlecitinib 50mg seemed to exhibit fewer adverse effects in the high-dose groups of oral JAK inhibitors and might be an optimal choice to balance safety and efficacy.The majority of JAK inhibitors exhibited acceptable short-term safety profiles. To enhance the applicability and accuracy of our research, further head-to-head trials with longer follow-up periods are needed.